Combining designer receptors exclusively activated by designer drugs and neuroimaging in experimental models: A powerful approach towards neurotheranostic applications. (3rd February 2020) - Peeters, Lore M.; Missault, Stephan; Keliris, Aneta J.; Keliris, Georgios A.
Abstract : The combination of chemogenetics targeting specific brain cell populations with in vivo imaging techniques provides scientists with a powerful new tool to study functional neural networks at the whole‐brain scale. A number of recent studies indicate the potential of this approach to increase our understanding of brain function in health and disease. In this review, we discuss the employment of a specific chemogenetic tool, designer receptors exclusively activated by designer drugs, in conjunction with non‐invasive neuroimaging techniques such as PET and MRI. We highlight the utility of using this multiscale approach in longitudinal studies and its ability to identify novel brain circuits relevant to behaviour that can be monitored in parallel. In addition, some identified shortcomings in this technique and more recent efforts to overcome them are also presented. Finally, we discuss the translational potential of designer receptors exclusively activated by designer drugs in neuroimaging and the promise it holds for future neurotheranostic applications. Abstract :